Impact of intercontinental pollution transport on North American ozone air pollution: an HTAP phase 2 multi-model study - Huang, Min (Atmos Chem Phys, 2017)
The recent update on the US National Ambient Air Quality Standards (NAAQS) of the ground-level ozone (O(3)/ can benefit from a better understanding of its source contributions in different US regions during recent years. In the Hemispheric Transport of Air Pollution experiment phase 1 (HTAP1), various global models were used to determine the O(3) source–receptor (SR) relationships among three continents in the Northern Hemisphere in 2001. In support of the HTAP phase 2 (HTAP2) experiment that studies more recent years and involves higher-resolution global models and regional models’ participation, we conduct a number of regional-scale Sulfur Transport and dEposition Model (STEM) air quality base and sensitivity simulations over North America during May–June 2010. STEM’s top and lateral chemical boundary conditions were downscaled from three global chemical transport models’ (i.e., GEOS-Chem, RAQMS, and ECMWF C-IFS) base and sensitivity simulations in which the East Asian (EAS) anthropogenic emissions were reduced by 20 %. The mean differences between STEM surface O(3) sensitivities to the emission changes and its corresponding boundary condition model’s are smaller than those among its boundary condition models, in terms of the regional/period-mean (<10 %) and the spatial distributions. An additional STEM simulation was performed in which the boundary conditions were downscaled from a RAQMS (Realtime Air Quality Modeling System) simulation without EAS anthropogenic emissions. The scalability of O(3) sensitivities to the size of the emission perturbation is spatially varying, and the full (i.e., based on a 100% emission reduction) source contribution obtained from linearly scaling the North American mean O(3) sensitivities to a 20% reduction in the EAS anthropogenic emissions may be underestimated by at least 10 %. The three boundary condition models’ mean O(3) sensitivities to the 20% EAS emission perturbations are ~8% (May–June 2010)/~11% (2010 annual) lower than those estimated by eight global models, and the multi-model ensemble estimates are higher than the HTAP1 reported 2001 conditions. GEOS-Chem sensitivities indicate that the EAS anthropogenic NO(x) emissions matter more than the other EAS O(3) precursors to the North American O(3), qualitatively consistent with previous adjoint sensitivity calculations. In addition to the analyses on large spatial–temporal scales relative to the HTAP1, we also show results on subcontinental and event scales that are more relevant to the US air quality management. The EAS pollution impacts are weaker during observed O(3) exceedances than on all days in most US regions except over some high-terrain western US rural/remote areas. Satellite O(3) (TES, JPL–IASI, and AIRS) and carbon monoxide (TES and AIRS) products, along with surface measurements and model calculations, show that during certain episodes stratospheric O(3) intrusions and the transported EAS pollution influenced O(3) in the western and the eastern US differently. Free-running (i.e., without chemical data assimilation) global models underpredicted the transported background O(3) during these episodes, posing difficulties for STEM to accurately simulate the surface O(3) and its source contribution. Although we effectively improved the modeled O(3) by incorporating satellite O(3) (OMI and MLS) and evaluated the quality of the HTAP2 emission inventory with the Royal Netherlands Meteorological Institute–Ozone Monitoring Instrument (KNMI–OMI) nitrogen dioxide, using observations to evaluate and improve O(3) source attribution still remains to be further explored.